2011
DOI: 10.1152/ajpheart.00570.2010
|View full text |Cite
|
Sign up to set email alerts
|

A constituent-based model of age-related changes in conduit arteries

Abstract: Tsamis A, Rachev A, Stergiopulos N. A constituent-based model of age-related changes in conduit arteries. Am J Physiol Heart Circ Physiol 301: H1286 -H1301, 2011. First published July 1, 2011; doi:10.1152/ajpheart.00570.2010.-In the present report, a constituent-based theoretical model of age-related changes in geometry and mechanical properties of conduit arteries is proposed. The model was based on the premise that given the time course of the load on an artery and the accumulation of advanced glycation end-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…This finding is compatible with increased tensile stretch at the inflection point of Θ -strips of adventitial-medial half of BAV-ATAA (1.28 ± 0.03) when compared with CTRL-ATA (1.13 ± 0.02) (Fig. 5), since more undulated fibers permit increased stretch before all fibers become engaged (straightened) (Tsamis et al, 2011). Nakashima et al (1990b), who assessed histologically the media of ATA dissecting aneurysms of type-A, reported that medial microstructure was characterized by decreased number of interlaminar elastin fibers.…”
Section: Discussionsupporting
confidence: 71%
“…This finding is compatible with increased tensile stretch at the inflection point of Θ -strips of adventitial-medial half of BAV-ATAA (1.28 ± 0.03) when compared with CTRL-ATA (1.13 ± 0.02) (Fig. 5), since more undulated fibers permit increased stretch before all fibers become engaged (straightened) (Tsamis et al, 2011). Nakashima et al (1990b), who assessed histologically the media of ATA dissecting aneurysms of type-A, reported that medial microstructure was characterized by decreased number of interlaminar elastin fibers.…”
Section: Discussionsupporting
confidence: 71%
“…This finding is consistent with the increased tensile stretch noted at the inflection point of Θ strips of the outer delaminated half of BAV-ATAA when compared with a nonaneurysmal ascending aorta, because more undulated fibers permit increased stretch before fibers become gradually engaged (ie, straightened). 30 Furthermore, we found 2 discrepancies in the architecture of RAD-oriented fibers across the media of TAV-ATAA with increasing age. Collagen AAU about the Z-axis was found to be increased within the outer-media.…”
Section: Discussionmentioning
confidence: 75%
“…Intersections density can impact the effective stiffness of the wall components and subsequently affect the mean and variance of the probability density function of fiber engagement. Attaching fibers to one another can stiffen the fiber ensemble by shifting the recruitment of the fibers to lower strains (decreased mean) and forcing the engagement to occur more abruptly (decreased variance) (Tsamis et al ., 2011). The end goal would be to model the fiber micro-architecture using finite-element methods.…”
Section: Discussionmentioning
confidence: 99%